Application of inverse modeling technique to describe hydrogeochemical processes responsible to spatial distribution of groundwater quality along flowpath - Tjahyo NugrohoAdji (Faculty of Geography, Universitas Gadjah Mada, 2005)
The main objective of this research is to define the mechanism model of chemical reactions, which are responsible to the spatial distribution of water quality along flowpath using inverse modeling technique. in addition, the Saturation Indices (SI) analysis was used to characterize the effect of geological condition toward dissolved constituent within the groundwater: Moreover, Mass Balance Modeling code was employed to describe the stoichiometry and hydrogeochemical processes along flowpath.Field survey was carried out in order to obtain the data of hydraulic head and electrical conductivity to construct flownets and tentatively illustrate the spatial distributions of shallow groundwater quality. Next, the flow line was applied to define the sampling position of groundwater and aquifer mineral. Laboratory analysis was conducted to identify the main phases and constrains of dissolved constituent within the groundwater. Afterwards, the application of NETPATH 2.1.3 and Phreeqc Interactive 2.8 for Windows software aid to model the Mass Balance Calculation in order to account the prevailing hydrogeochemical reactions.The result shows that firstly, the aquifer within the research area can be grouped into several aquifer systems (i.e. denudational hill, colluvial plain, alluvial plain, and beach ridges) from recharge to discharge which generally have potential groundwater resources in terms of the depth and fluctuation of groundwater table. Secondly, flownets analysis gives three flowpaths that are plausible to be modeled in order to describe their hydrogeochemical reactions. Thirdly, the Saturation Indices (SI) analysis shows that there are a positive correlation between the mineral occurrence and composition and the value of SI from recharge to discharge. In addition, The Mass Balance Model indicates that dissolution and precipitation of aquifer minerals is dominantly change the chemical composition along flowpath and the rate of the mass transfer between two wells shows a discrepancy and be certain of the percentage of the nature of aquifer mineral. Lastly, there is an interesting characteristic of mass balance chemical reaction occurs which is the entire chemical reaction shows that the sum of smallest mineral fmmol/litre) will firstly always totally be reacted.